ROOT INDUCTION ON THE SHOOTS OF RUBBER TREE (Hevea brasiliensis) CLONE PB 260 THROUGH EX VITRO TECHNIQUE - Yusuf Sigit Ahmad Fauzan (Jurnal Bioteknologi dan Biosains Indonesia, 2023)
Rubber tree (Hevea brasiliensis) is a crucial plantation commodity for Indonesia's national development. However, the country's rubber productivity lags behind that of other rubber-producing nations. To address this, propagating rubber plants from superior clones through ex-vitro techniques becomes essential.. This study aimed to determine the optimal concentrations of IBA and NAA for root induction in rubber tree shoot explants. A factorial complete randomized design was employed, with the first factor being IBA concentration (0, 100, 200, 300, 400, and 500 ppm) and the second factor being NAA concentration (0, 50, 100, and 150 ppm). The results revealed that the percentage of surviving explants after induction with IBA and NAA did not significantly differ. The rooted explants were obtained using the following treatments: IBA 200 ppm and NAA 0 ppm, IBA 200 ppm and NAA 50 ppm, IBA 300 ppm and NAA ppm, and IBA 400 ppm and NAA 0 ppm. Various concentrations of IBA and NAA did not significantly affect root formation in rubber tree shoot explants.